2000
DOI: 10.1029/1999gl011280
|View full text |Cite
|
Sign up to set email alerts
|

Seismic evidence for a thinner mantle transition zone beneath the South Pacific Superswell

Abstract: Abstract.Broadband seismograms recorded by the seismic stations deployed on oceanic islands in the South Pacific for two deep earthquakes in 1998 are used to investigate the mantle transition zone structure beneath the South Pacific, where a large-scale hot plume might ascend from the core-mantle boundary (CMB).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The depressions caused by the slabs have been studied by many authors; depression of 20~30 km beneath Tonga (Niu and Kawakatsu 1995) and up to about 50 km beneath Izu-Bonin (e.g., Collier et al 2001). Elevation of the 660 km discontinuity by 10-20 km is also reported in areas related to hot plumes such as Hawaii (Li et al 2000) and the South Pacifi c (Niu et al 2000). If the topography of the discontinuity is caused only by the effect of temperature on the phase boundary, an elevation of 20 km corresponds to a temperature elevation of about 1300 K and a depression of 50 km corresponds to a temperature decrease of about 3000 K, which implies unusually if not impossibly large temperature variations.…”
Section: The 660 Km Seismic Discontinuity and The Post-spinel Transfomentioning
confidence: 96%
“…The depressions caused by the slabs have been studied by many authors; depression of 20~30 km beneath Tonga (Niu and Kawakatsu 1995) and up to about 50 km beneath Izu-Bonin (e.g., Collier et al 2001). Elevation of the 660 km discontinuity by 10-20 km is also reported in areas related to hot plumes such as Hawaii (Li et al 2000) and the South Pacifi c (Niu et al 2000). If the topography of the discontinuity is caused only by the effect of temperature on the phase boundary, an elevation of 20 km corresponds to a temperature elevation of about 1300 K and a depression of 50 km corresponds to a temperature decrease of about 3000 K, which implies unusually if not impossibly large temperature variations.…”
Section: The 660 Km Seismic Discontinuity and The Post-spinel Transfomentioning
confidence: 96%
“…Lee and Grand (1996) observed at the East Pacific Rise in SS precursors the 410 and 660 close to their normal depths. Niu et al (2000Niu et al ( , 2002 identified at the South Pacific superswell the transition zone thinned by 15 km. Niu et al (2000Niu et al ( , 2002 identified at the South Pacific superswell the transition zone thinned by 15 km.…”
Section: Africamentioning
confidence: 97%
“…Other four hotspots are located at the edges of the superplume (Fig. Under the hotspots in the South Pacific superswell, the MTZ is generally thinner than that of the global average (Niu and Inoue 2000;Deuss 2007;Suetsugu et al 2009), and the PMPT is generally higher (Courtier et al 2007). In the upper mantle and the MTZ southwest of the Samoa hotspot, the subducting Tonga slab is clearly imaged as a high-velocity (high-V) zone.…”
Section: Pacific Hotspotsmentioning
confidence: 99%